Re-designing the traditional classroom setting in order to include the Special Educational Needs and create a new inclusive classroom - Bagnariol, Silvio (Formazione & insegnamento, 2017)
The setting in parallel rows of the traditional classroom facilitates the mechanisms of “micro-exclusion” (D’Alessio, 2011) and “periphery” (Dovigo, 2007) of all students, especially of those with Special Educational Needs. Indeed, the usual setting of the classroom facilitates only few education opportunities (D’Alonzo, 2012), that produces ‘‘isolation of the context “(Ellerani, 2014) in particular way of the students with any problem of “Human Functioning” (Ianes & Macchia, 2009). Instead, in the new inclusive classroom should be created learning agentive contexts (Sen, 2000) in which promote self-learning and the ecology of the action (Morin, 2005) of all students. For this purpose, new fully inclusive settings (Booth & Ainscow, 2008) can be achieved by modifying the geometry of the classroom, by enriching the traditional setting or by a new-design. Without radical intervention on the building but thanks to the acquisition of new inclusive skills of the teachers, this solution allows to differentiate the whole space of the classroom in different places of learning: the places to learn in mini-group, where the students find the objects of action, the analog source material and the new technologies. Therefore, the classroom becomes a single multimodal context of learning where the students with Special Educational Needs use their strategic languages and develop their talents (Margiotta, 1997).